Postcard from Rónán Ceannt to his 'Grany' Elizabeth O'Brennan from Ballybunion, Co. Kerry - Ceannt, Ronán, 1906-; O'Brennan, Elizabeth, d. 1930; Wain, Louis, 1860-1939 (1917)
Postcard includes an image of cats building sandcastle at 'The Sand Castle Competition' by Louis Wain.
Postcard is addressed to Mrs. O'Brennan at "44, Oakley Road / Ranelagh / Dublin ".
Keywords: Ceannt, Ronán -- 1906- -- Correspondence; O'Brennan, Elizabeth, -- d. 1930 -- Correspondence; Ireland -- History -- 1910-1921; Kerry (Ireland)